Relación entre la gestión financiera y de gobernanza y la rentabilidad de la Caja Municipal de Ahorro y Crédito de Arequipa durante el periodo 2020 – 2024 - Saenz Torrejon, Ricardo Erasmo (2025)
This research aimed to analyze the relationship between financial management, governance, and profitability of the Caja Municipal de Ahorro y Crédito de Arequipa (CMAC-Arequipa) during the period 2020 2024. Using a quantitative, non-experimental, and correlational design, the study combined historical financial data with normalized indices derived from surveys conducted with the institution’s executive staff. The main findings reveal that both operational efficiency and the quality of governance have a significant influence on institutional profitability, measured through ROE and EBITDA. Statistically significant and positive correlations were found between the financial management index, staff productivity, regulatory compliance, institutional transparency, and financial performance indicators. These results demonstrate that an institutional strategy that integrates efficient financial management with strong governance leads to sustainable levels of profitability, even in economically adverse contexts. This research provides empirical evidence on the relevance of aligning internal control systems, transparency, and operational efficiency as key pillars of profitability in microfinance institutions. The findings have practical implications for designing organizational policies focused on financial sustainability through sound institutional governance.